Perception and transformation of the concept of good governance in the post-Soviet space - Asryan, Narine (YSU Journal of International Affairs, 2023)
The discussion of the main provisions of the concept of good governance became relevant, especially since the end of the XX century that in world practice coincided with the collapse of the USSR and the formation of new independent states. In the created conditions the newly independent countries were forced to reform their management systems and follow the path of development in accordance with the standards set by the developed countries, which was quite problematic and difficult to implement in this period.This article analyzes the structural and substantive aspects of the concept of good governance, the features of understanding and transformation of the considered concept in the post-Soviet space. In particular, it is discussed what are the motives and consequences of the transformation of the traditional perception of the components of the concept of effective management in the post-Soviet space, as well as the role of international organizations (UN, World Bank, etc.) in these trends. The main question is whether to borrow the western standards of good governance or to develop and implement our own concept taking into account the features of the historical and cultural heritage and social development. The article also gives forecasts about what basic elements should be added to the concept of good governance and what are the promising opportunities for their implementation in the post-Soviet space.
Keywords: good governance; government effectiveness indicators; post-Soviet area; developing and transitional state; government effectiveness; transparency; reform; development